Flexural Behaviour of Nanoclay filled Chopped Basalt and Glass Fibres Composites - Emi Nor Ain Mohammad, Nurul; Jumahat, Aidah; Raihanah Hashim, Ummu; Syarah Iffah Azizi, Nur (International Journal of Engineering and Technology, 2018)
Natural fibres have attracted researcherâ€™s attention due to their advantages such as abundance of resources, good mechanical properties and low density. In order to increase the usage of natural fibre, lots of researches have been conducted on natural fibres as reinforcement to polymer matrix. In this study, natural and synthetic fibres were used in order to determine and compare the properties of these materials in terms of their flexural strength, modulus and failure strain. Chopped natural mineral based fibre namely basalt and synthetic fibre namely glass of 5 mm length were used. Epoxy resin was used as the polymer where the drawback of this material is its brittleness. In order to overcome this weakness, nanoclay filler of 1, 3, 5 wt% was used to increase the stiffness of the epoxy resin. Therefore, the aim of this study is to evaluate the effect of nanofillers content on different types of chopped fibres reinforced polymer composites. The flexural tests were conducted according to ASTM D790 with specimen size of 4mm thickness, 10 mm width and 78mm length with 60mm support span. The results indicated that nanoclay filled-chopped GFRP exhibited the highest flexural properties at 5wt% nanoclay while, nanoclay filled-chopped BFRP showed the best flexural properties at 3 wt% nanoclay.Â